The Effect of the Discount Rate on Depletion of Exhaustible Resources - Farzin, Y. Hossein (Journal of Political Economy, 1984)
This paper argues that, despite its widespread acceptance in the literature, the basic proposition that a reduction (an increase) in the discount rate leads to greater conservation (faster depletion) of an exhaustible resource is not generally valid. It shows that the effect of the discount rate on the rate of resource depletion depends on capital requirements for production of the substitute and extraction of the resource and on the size of the resource stock. In fact, it shows that there always exist at least two ranges of the resource stock size for which the effect is opposite to that conventionally believed.